﻿Nineteen new species of Desmopachria Babington, 1841 (Coleoptera, Adephaga, Dytiscidae, Hydroporinae, Hyphydrini) with notes on the taxonomy of the genus - Kelly B. Miller (ZooKeys, 2022)
Nineteen new species of Desmopachria Babington, 1841 are described from multiple species groups. Two new species groups are erected, the Desmopachria apicodente species group and the Desmopachria bifurcita species group. Desmopachria divergens sp. nov. (Venezuela), Desmopachria lineata sp. nov. (Venezuela), Desmopachria surinamensis sp. nov. (Suriname), and Desmopachria tenua sp. nov. (Guyana) are described in Desmopachria but are not assigned to a species group. Desmopachria apicodente sp. nov. (Guyana, Venezuela), Desmopachria lateralis sp. nov. (Venezuela), and Desmopachria tumida sp. nov. (Venezuela) are described in the new Desmopachria apicodente species group and are the only members of the group. Desmopachria bifurcita sp. nov. (Peru), and Desmopachria lata sp. nov. (Brazil) are described in the new Desmopachria bifurcita group. Other members of the Desmopachria bifurcita group are Desmopachria bifasciata Zimmermann, Desmopachria bolivari Miller, Desmopachria ovalis Sharp, and Desmopachria varians (each previously “ungrouped”). Desmopachria pseudocavia sp. nov. (Venezuela) is described in the Desmopachria convexa-signata species group. Desmopachria wolfei sp. nov. (Venezuela) is described in the Desmopachria nitida species group. Desmopachria angulata sp. nov. (Guyana, Suriname), Desmopachria emarginata sp. nov. (Guyana, Suriname, Venezuela), Desmopachria imparis sp. nov. (Guyana), Desmopachria impunctata sp. nov. (Suriname, Venezuela), and Desmopachria truncata sp. nov. (Guyana, Suriname) are described in the Desmopachria portmanni-aldessa species group. Desmopachria bisulcata sp. nov. (Suriname), and Desmopachria irregulara sp. nov. (Venezuela) are described in the Desmopachria portmanni-portmanni species group. Desmopachria robusta sp. nov. (Venezuela) is described in the Desmopachria striola species group. A key to the species groups is included. Male genitalia are figured for all new species and dorsal habitus images are provided for most new species.